Vector Auto Regressive (VAR) Model Approach in the Capital Market - Suyanto, Suyanto (Magister Akuntansi Universitas Pancasila, 2023)
As an important instrument in the economy, the capital market requires indicators to determine its growth. One of the influencing indicators is the Composite Stock Price Index (IHSG) with various factors that influence it. This research aims to test and analyze the relationship between inflation, exchange rate, BI-rate, and the amount of money in circulation (M2) on the IHSG for the period January 2017-March 2022 using the Vector Autoregression (VAR) method analyzed with Eviews 12. Process results The data in the research provides evidence that the variables only have a one-way relationship, where the R-squared value shows that the independent variables in the model can explain the changes in the dependent variable that occur. A high F-Stat value in the data processing results indicates that the variables in the model have a simultaneous influence on the dependent variable. The implications of this research can provide insight to market players and regulators regarding macroeconomic factors that can influence capital market growth.